Pembinaan Komunitas Ramah Lingkungan (Eco Community) Berbasis Pelatihan Green Lifestyle: Eco-Friendly Community Development Through Green Lifestyle Training - Restya, Winda Putri Diah; Septiawati, Sriana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Environmental challenges in Indonesia, such as deforestation, water pollution, and a lack of public awareness regarding environmental sustainability, present significant obstacles to achieving sustainable development goals. Despite growing awareness of environmental issues, eco-friendly behaviors, and lifestyle changes among the population remain limited. This community service initiative seeks to establish a